2021
DOI: 10.3390/telecom2040022
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Techniques in RF Energy Harvesting Circuits

Abstract: The exigency for continuous use of electrical devices has created greater demands for electricity along with more efficient transmission techniques. Energy from natural resources can be solar, thermal, vibration, friction, or Radio Frequencies (RF) signals. This state-of-the-art work provides a summary of RF energy harvesting techniques and can be used as a guide for the manufacture of RF energy scavenging modules. The use of Radio Frequency (RF) Energy Harvesting (EH) technique contributes to the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Combining battery-less powering devices in a broad spectrum of applications and RF power delivered with lightweight and cost-effective, ecofriendly printed electronics techniques could widen the application of IoT devices. However, knowledge about the capability of printed electronics techniques to manufacture rectenna components is bounded by the limited number of presented appli-cations in related reviews, focused on specific aspects of the RF energy harvesting and wireless power transfer domain (such as RF EH in specific applications, [1,13,68,173] hardware, and design methodologies, [23,55,66] RF powered wireless networks, [100] protocols design, [174] radiation sources, [23] ) or different spectrums of printed electronics applications. [6,24,137,[175][176][177] In this review, we present printed electronics techniques found to be the best candidates for manufacturing radio frequency energy harvesting and wireless power transfer systems and describe rectenna components manufactured by them.…”
Section: Printed Electronics Techniques Applications In Energy Harves...mentioning
confidence: 99%
See 2 more Smart Citations
“…Combining battery-less powering devices in a broad spectrum of applications and RF power delivered with lightweight and cost-effective, ecofriendly printed electronics techniques could widen the application of IoT devices. However, knowledge about the capability of printed electronics techniques to manufacture rectenna components is bounded by the limited number of presented appli-cations in related reviews, focused on specific aspects of the RF energy harvesting and wireless power transfer domain (such as RF EH in specific applications, [1,13,68,173] hardware, and design methodologies, [23,55,66] RF powered wireless networks, [100] protocols design, [174] radiation sources, [23] ) or different spectrums of printed electronics applications. [6,24,137,[175][176][177] In this review, we present printed electronics techniques found to be the best candidates for manufacturing radio frequency energy harvesting and wireless power transfer systems and describe rectenna components manufactured by them.…”
Section: Printed Electronics Techniques Applications In Energy Harves...mentioning
confidence: 99%
“…[63][64][65] A rectenna consists of an antenna, impedance matching network, and rectifier (sometimes also additionally functioning as a voltage multiplier). [66] The antenna intercepts RF energy propagating through space. Then, a rectifier converts obtained energy, maximized by the impedance matching network, [57] into the direct current with desired voltage amplitude.…”
Section: Rectenna Design and Efficiency In Eh And Wpt System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Some directly propose solutions to manage the energy harvested without being interested in the processes of transforming RF waves into DC electrical energy suitable for powering the WS [ 14 , 15 ]. Other studies deal only with RF/DC transformation without examining rectenna powering techniques [ 16 , 17 ]. The solutions for minimizing WSs’ energy budget are often ignored or treated independently.…”
Section: Comparison With Related Reviewsmentioning
confidence: 99%
“…If it still consumes conventional energy, that would have a serious impact on the economic and social development of many countries [1]. Due to this problem, many researchers have developed new forms of renewable energy, such as solar energy [2], biomass energy [3], wind energy [4], thermal energy [5], and radio frequency energy (RF), such as the digital TV, mobile, and WiFi frequency range [6][7][8][9][10][11][12][13][14][15]. Due to the foregoing, researchers have been interested in developing the field of energy harvesting from radio frequency (RF) that uses a receiver antenna and AC to DC power conversion circuit.…”
Section: Introductionmentioning
confidence: 99%